The People and the Word : Reading Native Nonfiction - Warrior, Robert Allen (Book collections on Project MUSE., 2005)
The People and the Word explores how the Native tradition of nonfiction has both encompassed and dissected Native experiences. Robert Warrior traces a history of American Indian nonfiction writing, including Pequot intellectual William Apess's autobiographical works; the Osage Constitution of 1881; accounts of boarding school in the late 1880s; and modern Kiowa writer N. Scott Momaday's essay "The Man Made of Words."